2010
DOI: 10.1016/j.toxlet.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Generation of T cell responses targeting the reactive metabolite of halothane in mice

Abstract: Immune-mediated adverse drug reactions (IADRs) represent a significant problem in clinical practice and drug development. Studies of the underlying mechanisms of IADRs have been hampered by the lack of animal models. Halothane causes severe allergic hepatitis with clinical features consistent with an IADR. Our ultimate goal is to develop a mouse model of halothane hepatitis. Evidence suggests that adaptive immune responses targeting liver protein adducts of the reactive metabolite (TFA) play an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Intraperitoneal injection of halothane in oil induced liver injury in mice and generated an innate immune response (You et al, 2006). Mouse strain-, age-, and sex-dependent variations in the severity of this injury were observed, including female sex and older age (Cheng et al, 2009You et al, 2010), which are analogous to the risk factors in humans. Moreover, this injury was increased by agents such as poly-IC that act through Toll-like receptors (Cheng et al, 2009).…”
Section: Halothane-induced Liver Injurymentioning
confidence: 98%
“…Intraperitoneal injection of halothane in oil induced liver injury in mice and generated an innate immune response (You et al, 2006). Mouse strain-, age-, and sex-dependent variations in the severity of this injury were observed, including female sex and older age (Cheng et al, 2009You et al, 2010), which are analogous to the risk factors in humans. Moreover, this injury was increased by agents such as poly-IC that act through Toll-like receptors (Cheng et al, 2009).…”
Section: Halothane-induced Liver Injurymentioning
confidence: 98%
“…Multiple hepatic proteins including calreticulin, protein X, carboxylesterase and the pyruvate dehydrogenase complex are conjugated with TFA-chloride indicating that multiple peptide epitopes will be available for T cells [37]. Although the nature of the drugspecific cellular immune response in patients with liver injury has not been studied, You et al found that both CD4 + and CD8 + T cells were activated in mice in response to the TFAreactive metabolite [38].…”
Section: Mechanistic Features Of Drug Hypersensitivity Reactionsmentioning
confidence: 99%
“…), and induce T‐cell responses (You et al . ). These observations raised the possibility that the higher TFA in MOG‐A was contributing to increased disease severity.…”
Section: Discussionmentioning
confidence: 97%
“…TFA has recently been shown to act as an allosteric modulator of glycine receptors, increasing receptor activity at lower glycine concentrations (Tipps et al 2012) and previously was shown to activate ATP sensitive potassium channels (Han et al 2001). In vivo, TFA can trifluoroacetylate amino groups in proteins and phospholipids (Satoh et al 1985), which can elicit antibody responses (Trudell et al 1991;Furst et al 1997), increase proinflammatory cytokine production (You et al 2006), and induce T-cell responses (You et al 2010). These observations raised the possibility that the higher TFA in MOG-A was contributing to increased disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation